Research on the Development Dilemmas and Optimization Paths of Community-Based Music Education for Older Adults from the Perspective of Active Aging - Jiang, Yi; Hou, Bo; Wu, Qingfeng (Education Insights, 2026)
With the continuous advancement of active aging strategies and the systematic improvement of lifelong education systems, cultural elderly care has evolved into a core developmental direction of modern elderly service undertakings. As a vital grassroots carrier of community aesthetic education and cultural elderly care, community-based music education for older adults effectively improves the cognitive status of aging populations, facilitates their social participation, alleviates negative psychological emotions, and boosts the overall quality of later life. Adopting a mixed research methodology based on active aging and lifelong education theories, this study systematically explores the current developmental status and practical bottlenecks of community-based music education for older adults. The findings reveal that this grassroots educational model is plagued by rigid curriculum frameworks, insufficient professional teaching teams, low learning initiative among older participants, inadequate grassroots supporting facilities, and prevalent teaching homogenization. These multifaceted dilemmas stem from delayed policy implementation, unbalanced public resource allocation, inadequate teaching adaptability, and individual cognitive discrepancies. Combining grassroots practical experiences and latest academic achievements, this study develops localized and implementable optimization strategies for educational quality improvement. It effectively remedies the existing research imbalance that overemphasizes educational practices in universities for the elderly while ignoring grassroots community scenarios, providing solid theoretical references and practical implications for the high-quality development of grassroots elderly aesthetic education and the comprehensive implementation of active aging strategies.